UTILIZATION OF NARROW LAND WITH VERTICULTURE TECHNIQUES IN URBAN AREA - Hartono, Rudi; Hartini, Kansih Sri; Purwoko, Agus (Talenta Publisher Universitas Sumatera Utara, 2021)
Urban areas are generally in the form of housing with narrow land. The purpose of this activities was to use narrow land for farming with verticulture techniques. The activity was held in Puri Zahara 1 Residence, Medan Tuntungan District. which is a residential area with narrow land. The method used was to provide training to housewife to be able to utilize the land with verticulture techniques. Housewives was briefed in order to be able to use the land using existing materials, especially verticulture techniques. The material used in verticulture techniques was paralon. The result of this dedication is that the community can utilize small land, especially in residential areas with verticulture techniques to plant flowers or vegetable crops, so that the house becomes greener and livelier. With this verticulture technique, more vegetable or fruit crops can be planted. some plants planted include lettuce, water spinach, flowers